Divine and creaturely agency in Genesis 1 - Chambers, Nathan (Scottish journal of theology, 2019)
The interaction between God and creatures is central to biblical narratives. There are several possible models for understanding the relationship between divine and creaturely agency. This article argues that a 'non-competitive' model for the interaction of divine and creaturely agency allows for a coherent interpretation of various features of Genesis 1 where alternative models lead to confusion. Since this 'non-competitive' model is historically related to creatio ex nihilo, it raises once again the question of the suitability of creatio ex nihilo for biblical interpretation.